Quoted spreads and trade imbalance dynamics in the European treasury bond market - Guglielmo Maria Caporale; Alessandro Girardi; Paolo Paesani (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Using high-frequency transaction data for the three largest European markets (France, Germany and Italy), this paper documents the existence of an asymmetric relationship between market liquidity and trading imbalances: when quoted spreads rise (fall) and liquidity falls (increases) buy (sell) orders tend to prevail. Risk-averse market-makers, with inventory-depletion risk being their main concern, tend to quote wider (narrower) spreads when they think bond appreciation is more (less) likely to occur. It is also found that the probability of being in a specific regime is related to observable bond market characteristics, stock market volatility, macroeconomic releases and liquidity management operations of the monetary authorities.
Keywords: G1; G15; C32; C33; 330; Liquidity; trading activity; Treasury bond market; Europe; commonality